2021
DOI: 10.1155/2021/5572011
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Durability Behaviour and Optimization of Concrete with Triple‐Admixtures Subjected to Freeze‐Thaw Cycles in Salt Solution

Abstract: In the seasonal frozen area of northeast China, cement concrete is usually in a working environment of cold climate and chlorine erosion coupling effect. In general, with a reasonable addition of air entraining agent (AEA) and multimineral admixtures such as fly ash, blast furnace slag, and silica fume, the durability of cement concrete under the effects of freeze-thaw and salt solution can be significantly improved in cold regions. However, due to several more compositions of cement concrete with multiple min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 58 publications
5
9
0
Order By: Relevance
“…From Figure 5(b), it can be seen that the 28-day flexural strength of control cement concrete is 4.95 MPa, and the flexural strength of cement concrete is 4.48 MPa, 4.25 MPa, and 3.92 MPa when the FA contents are 10%, 20%, and 30%, which indicates that the flexural strength of cement concrete decreases with the increase of FA content, which is line with the findings of Mardani-Aghabaglou et al [51]. It can be seen from Figure 5(c) that the surface resistivity increases with the increase of FA content, and the surface resistivity changes slightly with the increase of FA content in the range of 10%∼ 20%, as previously described in [59]. In Figure 5(d), the rapid chloride permeability of control cement concrete in 28 days is 1951.5 C. With the increase of FA content, the rapid chloride permeability decreases.…”
Section: Influence Analysis Of Mineral Admixtures and Air Content On Physical And Mechanical Performances Of Concretessupporting
confidence: 90%
See 4 more Smart Citations
“…From Figure 5(b), it can be seen that the 28-day flexural strength of control cement concrete is 4.95 MPa, and the flexural strength of cement concrete is 4.48 MPa, 4.25 MPa, and 3.92 MPa when the FA contents are 10%, 20%, and 30%, which indicates that the flexural strength of cement concrete decreases with the increase of FA content, which is line with the findings of Mardani-Aghabaglou et al [51]. It can be seen from Figure 5(c) that the surface resistivity increases with the increase of FA content, and the surface resistivity changes slightly with the increase of FA content in the range of 10%∼ 20%, as previously described in [59]. In Figure 5(d), the rapid chloride permeability of control cement concrete in 28 days is 1951.5 C. With the increase of FA content, the rapid chloride permeability decreases.…”
Section: Influence Analysis Of Mineral Admixtures and Air Content On Physical And Mechanical Performances Of Concretessupporting
confidence: 90%
“…It can be seen from Figure 8(d) that the rapid chloride permeability of concrete can be effectively reduced in the case of double mixing, but when 6% SF is added, the rapid chloride permeability is only 287.5 C, which indicates that SF can effectively reduce the rapid chloride permeability of concrete. is is similar to the previous research results [39,43,59]. e results showed that the mechanical properties of the concrete are better than that of the control cement concrete, which indicates that the hydration and secondary hydration of mineral admixtures are sufficient in the process of strength formation, which can provide strength for the concrete [1,34,58].…”
Section: Influence Of Multimineral Admixturessupporting
confidence: 90%
See 3 more Smart Citations